Turning points and myths of German memory - Olick, Jeffrey K. 1964- (Zeithistorische Forschungen, 2009)
What have been the contributions of social memory studies to the discourse of German history, particularly about the Nazi past? This essay seeks to distinguish between the memory boom in politics and culture and the more durable insights of social theory and historiography about memory, including insights about this memory boom itself. In particular, it explores mythologies of ‘turning points’ in the discourse of memory, arguing that the attribution of such turning points is often overstated. To be sure, 1989 did mark significant ruptures. But comparing present debates to the Historikerstreit (historians’ dispute) of the mid-1980s, and the Historikerstreit to earlier debates shows that as much has stayed the same as has changed. We remember not just the Nazi past, but the previous ways in which we have remembered the Nazi past, and our mnemonic practices are as much comments on earlier practices as on the event itself.